A guide to effective writing - Aimufuwa, Vera (Nigeria, APC production ventures, 2013)
This book provide a detailed guide on how develop skill in reading and writing.
includes bibliographic 184-189
asm, 23/04/21
Loans
Keywords: English language; Letter writing; Commercial correspondence